2022
DOI: 10.3390/ijerph191711003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Body Composition in CrossFit® Athletes and the Relation with Their Results in Official Training

Abstract: CrossFit® is a high-intensity sport that combines weightlifting, gymnastic skills, and cardiovascular exercises. To find the anthropometric references that define the optimal body composition, it is essential to first find an optimal body composition for one’s physical preparation. The objective of this study is to describe the anthropometric characteristics of 27 Spanish CrossFit® athletes, 19 males aged 39 years old (24–44) and 8 females aged 28 years old (23–40), and how these characteristics influenced the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In fact, in our study, it has been observed that muscle mass also increases as biological maturation advances, showing that early maturers have the most muscle mass. In previous research with adult athletes, where they also observed elevated BMI values, they concluded that it was due to the high development of muscle mass or fat-free mass, and to correctly classify the athlete population as overweight and obese, fat mass should be used [63,64]. However, these investigations were carried out in the adult athlete population, and this research is one of the first that assesses the classification of BMI in adolescent athletes and relates it to maturation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In fact, in our study, it has been observed that muscle mass also increases as biological maturation advances, showing that early maturers have the most muscle mass. In previous research with adult athletes, where they also observed elevated BMI values, they concluded that it was due to the high development of muscle mass or fat-free mass, and to correctly classify the athlete population as overweight and obese, fat mass should be used [63,64]. However, these investigations were carried out in the adult athlete population, and this research is one of the first that assesses the classification of BMI in adolescent athletes and relates it to maturation.…”
Section: Discussionmentioning
confidence: 90%
“…However, these investigations were carried out in the adult athlete population, and this research is one of the first that assesses the classification of BMI in adolescent athletes and relates it to maturation. Therefore, more research is needed, both in handball players and in other sports modalities, to find out whether biological maturation influences BMI or whether the increase in BMI is only due to the development of muscle mass caused by this process [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…This method was selected over other approaches because it is a noninvasive technique validated in cadavers for body composition measurements and is both portable and cost effective (20,26). Moreover, this method is also valid for athletes or muscular individuals (16,19). Notably, the technical measurement error for the intraobserver anthropometrist at ISAK Level II is reported to be #7.5% for skinfolds and # 1.5% for breadths, girths, body mass, and height (8), which ensures accurate estimates of body composition with a low level of error.…”
Section: Methodsmentioning
confidence: 99%
“…Historically, researchers have attempted to estimate different anthropometric variables and body composition measures using diverse techniques, such as dual-energy x-ray absorptiometry (DXA), bioelectrical impedance (BI), anthropometry, and other indirect and doubly indirect methods (15). Anthropometry is a scientific discipline that assesses shape, size, composition, proportionality, and bodily function to establish their relationship with nutrition, exercise, and sports performance (19,21). To ensure consistency in approaches, terminology, and practices, as well as to obtain precise and valid measurements, the International Society for the Advancement of Kinanthropometry (ISAK) developed a standardized protocol that facilitates improved data comparison and reproducibility across different laboratories (6).…”
Section: Introductionmentioning
confidence: 99%
“…CrossFit® stands out as a sport that has witnessed substantial growth in athlete participation over the past two decades [ 1 ]. Characterized by high-intensity regimens integrating weightlifting, calisthenics, and cardiovascular exercises, its workouts exhibit notable variability due to the comprehensive array of exercises involved [ 2 ]. The foundation of CrossFit® revolves around consistently varying functional movements at high intensity to enhance fitness and promote health [ 3 ].…”
Section: Introductionmentioning
confidence: 99%